IDENTIFICATION OF FOOD DIVERSIFICATION ON JAVA ISLAND USING ARCGIS - Murtako, Amir; Hanifa, Faiqa Hadya; Effatha, Eidelwise Gloria; Nursari, Sri Rezeki Candra; Maspiyanti, Febri (Jurnal Pilar Nusa Mandiri, 2025)
Indonesia is addressing the challenges of food security and consumer preference also known as Food diversification. The research aims to analyze the potential of various local food sources as alternatives to rice, which is the dominant staple food in Indonesia, with a particular focus on geographic implications. Although local carbohydrate sources like corn, potatoes, and tubers are available, their adoption is limited and understudied in relation to geographic distribution and consumer behavior. This study integrates survey data and GIS-based spatial analysis to evaluate local food diversification potential. Findings show that while 100% of respondents consume rice, 48.7% have tried alternatives, with limited availability (41.03%) and higher costs (17.95%) as key barriers. With 94.7% expressing willingness to adopt new staples, the results suggest GIS-based decision support systems can guide effective, region-specific food policy interventions.